Competing in cross-country skiing - Nilsson, B. H. (Bengt-Herman) (Sterling Pub. Co., 1974)
Discusses the techniques of cross-country skiing, the equipment and its upkeep, cross-country races and how to prepare for them, and champions of the sport.